2015
DOI: 10.1007/s00256-015-2155-z
|View full text |Cite
|
Sign up to set email alerts
|

Value of monoenergetic dual-energy CT (DECT) for artefact reduction from metallic orthopedic implants in post-mortem studies

Abstract: This study demonstrates that monoenergetic DECT images extrapolated at high energy levels significantly reduce metallic artefacts from orthopedic implants and improve image quality compared to SECT examination in forensic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 36 publications
2
22
0
1
Order By: Relevance
“…We found that the overall image quality improved with reduced artifacts using iMAR or DECT which is in line with similar studies [5,12,22]. Also, the optimal keVs for monochromatic images found here are similar to those found by others [4,23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the overall image quality improved with reduced artifacts using iMAR or DECT which is in line with similar studies [5,12,22]. Also, the optimal keVs for monochromatic images found here are similar to those found by others [4,23].…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that metal artifacts can also be reduced using virtual monochromatic images extracted from dual-energy CT (DECT) scans [4][5][6]. In DECT, two different energy spectra are used to acquire CT images [7].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies reported optimal monoenergetic levels ranging from 105 kV to 148 kV. [5][6][7][8] These studies varied in terms of the region imaged, material, and the geometry of the implants that may affect the optimal monoenergetic level.…”
Section: Discussionmentioning
confidence: 99%
“…Auch eine knöcherne Konsolidierung der Frakturen kann hiermit überprüft werden. Sollten umfangreiche Implantate einliegen, kann die Wahl einer Dual-Energy-Computertomografie sinnvoll sein [4]. Bei klinischem Verdacht auf eine Achs-oder Längenfehlstellung kann zusätzlich eine konventionelle Achsbeinstandaufnahme, bei Verdacht auf einen Rotationsfehler eine Rotationscomputertomografie indiziert sein.…”
Section: Analyse Der Fehlgeschlagenen Osteosyntheseunclassified